Au/CeO2-ZnO/Al2O3 as Versatile Catalysts for Oxidation Reactions: Application in Gas/Liquid Environmental Processes - Megías-Sayago, Cristina; Reina, Tomas Ramirez; Ivanova, Svetlana; Odriozola, Jose A. (Frontiers in Chemistry, 2019)
This work showcases the versatility of multicomponent gold based catalysts for environmental catalysis. We have designed a series of nanogold systems supported on Zn-doped ceria with excellent activity in gas phase reactions (i.e. total CO oxidation) and liquid phase processes such as the selective oxidation of glucose. In the CO oxidation the suitability of these materials is clearly demonstrated achieving full conversions even at sub-ambient conditions. As for the glucose oxidation our materials display high conversion values (always over 50%) and very importantly full or almost full selectivity towards gluconic acid – an added value platform chemical in the context of biomass upgrading routes. The key factors controlling the successful performance on both reactions are carefully discussed and compared to previous studies in literature. To our knowledge this is one of the very few works in catalysis by gold combining liquid and gas phase reactions and represents a step forward in the flexible behavior of nano gold catalysts.